ESBL-producing Enterobacterales in food and clinical samples: antimicrobial resistance organisms and genes in Chiang Mai, Thailand - Sirikwan Dokuta; Xiao Zhang; Peerapong Jeeno; Sayamon Hongjaisee; Sumed Yadoung; Phadungkiat Khamnoi; Bajaree Chuttong; Zhou Kai; Surat Hongsibsong (Scientific Reports)
Abstract Globally, food safety and security are negatively impacted by antimicrobial resistance (AMR). The emergence of resistance caused by extended-spectrum β-lactamases (ESBLs) during the AMR era has resulted in increased morbidity, longer hospital stays, and more costly treatment alternatives. This study aimed to detect the contamination of ESBL-producing Enterobacterales antibiotic-resistant bacteria and ESBL genes in food materials and clinical samples in Chiang Mai, Thailand. Microbial culture-based, molecular and nucleotide sequencing methods were used in this study. Of 279 food samples, chicken meat was the most contaminated with ESBL-producing organisms (50%), followed by pork meat (48%), and tomato (2%). The prevalence rate of ESBL-producing E. coli, K. pneumoniae and K. oxytoca were 15.41%, 2.15%, and 0.36%, respectively. Moreover, we detected 96.15% of bla CTX-M gene and 43.59% of bla TEM gene from these organisms. While of 39 clinical samples, 22 samples were ESBL-producing E. coli and 17 samples were ESBL-producing K. pneumoniae. The prevalence of bla CTX-M and bla TEM genes in these samples were 94.87% and 66.67%, respectively. These study findings raise concerns about the consumption of AMR bacteria. All parties involved in the supply chain for food production and consumption must engage in behavioral communication, excellent agricultural and industrial practices, and awareness-raising initiatives.